Cell dedifferentiation, callus induction and somatic embryogenesis in Crataegus spp - Taimori, N; Kahrizi, D; Abdossi, V; Papzan, A H (Cellular and Molecular Biology, 2016)
The present study describes the effects of light conditions, different kinds and concentrations of auxins [Naphthylacetic acid (NAA) and dichlorophenoxyacetic acid (2,4-D)] with cytokinin (Kin) in MS medium on callus induction and embryogenesis in Crataegus pseudoheterophylla, C. aronia and C.meyeri. At first leave explants sections were cultured on different combinations of plant growth regulators in dark and light for callus initiation and light conditions to evaluation the percentage and duration of survival, callus diameter, callus fresh weight and dry. Results of effects of plant growth regulators and light conditions on callus initiation revealed that highest percentage of callus initiation leaves in treatment (0.5 mg/l 2.4-D+0.5 mg/l KIN) for species C.pseudoheterophylla in dark conditions (100%). Dark conditions (100%) were more effective on callogenesis than light conditions (Photoperiodicity of 16-h and at light intensity of 40 µmol m-2 s-1). The callus induction of in vitro (64-100%) leaves was better than the ex vitro ones (0-100%). The combination of 2,4-D and Kin of in vitro leaves callogenesis has been indicated faster (one weeks) than the other combinations. The results also showed that the highest percentage (100%) and survival duration (6 months) was found in species C. pseudoheterophylla and C. meyeri in 0.1 mg/l 2,4.D + 0.5 mg/l KIN and 0.5 mg/l 2,4.D + 0.5 mg/l Kin. The minimum survival (0%) was absorbed in species C. aronia in 1 mg/l NAA. Maximum callus (10.63 and 10.00 mm respectively) was shown in 0.1 mg/l 2,4.D + 0.5 mg/l Kin and 0.5 mg/l 2,4.D + 0.5 mg/l Kin and was not significant differences after five week among species. The results showed that the highest fresh (1081.49 mg) and dry weight (506.88 and 506.98 mg respectively) was absorbed in species C. pseudoheterophylla in 0.1 mg/l 2,4.D + 0.5 mg/l Kin and 0.5 mg/l 2,4.D + 0.5 mg/l Kin. The embryogenesis was not occurred in any plant growth regulator combinations and species. The results of this study suggested that using 2,4-D with cytokinin (Kin) would be more beneficial for callogenesis.